2019
DOI: 10.1007/s10815-019-01638-z
|View full text |Cite
|
Sign up to set email alerts
|

What is the true place of a double stimulation and double oocyte retrieval in the same cycle for patients diagnosed with poor ovarian reserve? A systematic review including a meta-analytical approach

Abstract: Purpose This systematic review including a meta-analytical approach aims to investigate the safety and efficacy of employing a double ovarian stimulation (DuoStim) and a subsequent double oocyte retrieval in the same menstrual cycle, in poor ovarian reserve (POR) patients. Methods A systematic search of literature was performed in the databases of PubMed/MEDLINE, Embase, and Cochrane Central Library up until March 2019. Both prospective and retrospective cohort studies considered suitable for inclusion reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
0
26
1
2
Order By: Relevance
“…Baerwald et al has proposed three theories of follicle recruitment [28] : the theory of continuous recruitment, single recruitment theory, and the wave theory. The theory of continuous recruitment includes the interval between two ovulations [47]. During this time, the follicles begin to grow continuously and gradually disappear, and the dominant follicle is randomly selected after the corpus luteum has degenerated.…”
Section: Discussionmentioning
confidence: 99%
“…Baerwald et al has proposed three theories of follicle recruitment [28] : the theory of continuous recruitment, single recruitment theory, and the wave theory. The theory of continuous recruitment includes the interval between two ovulations [47]. During this time, the follicles begin to grow continuously and gradually disappear, and the dominant follicle is randomly selected after the corpus luteum has degenerated.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, researchers explored the new strategy of stimulation in the luteal phase both independently and in combination with standard stimulation protocols, introducing to the clinical field what is described as the protocol of double stimulation (DuoStim) [ 98 , 99 , 100 ]. As a result, DuoStim consists of an ordinary follicular phase stimulation (FPS) in combination with luteal phase stimulation (LPS) [ 15 , 101 ]. This approach has been associated with increased chances of a pregnancy being ensued.…”
Section: Managing Poor Ovarian Responsementioning
confidence: 99%
“…Data presented in the study of Kuang et al indicate that COS conducted in both FPS and LPS could enhance oocyte yield and subsequently the number of generated embryos, improving the IVF success rate [ 97 ]. Since then, several studies were conducted investigating the effectiveness of different DuoStim protocols employing different COS strategies [ 15 , 99 , 101 ]. A systematic review and meta-analysis, published by Sfakianoudis and colleagues, demonstrated that DuoStim approaches could effectively increase oocyte yield in the same menstrual cycle, and this is a significant outcome considering the time-sensitive nature of POR patients [ 15 ].…”
Section: Managing Poor Ovarian Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Evidenciamos que a utilização de testosterona transdĂ©rmica na dose de 25mg a cada 48h, maior do que as doses utilizadas em outros estudos em pacientes potencialmente más respondedoras (MASSIN et al, 2006;BALASCH et al, 2006;SIPE et al, 2010;FABREGUES et al, 2009;HOWLES;LEE, 2011;KIM et al, 2014;BOSDOU et al, 2016;DOAN et al, 2017) MASSIN et al, 2006, SIPE et al, 2009e BOSDOU et al, 2016 (BALASCH et al, 2006;FABREGUES et al, 2009;HOWLES;LEE, 2011e KIM et al, 2014 (SFAKIANOUDIS et al, 2019). No nosso estudo, a medida de tamanho de efeito de Cohen (COHEN et al, 1988)…”
Section: Discussionunclassified